Successful Global Collaborations in Higher Education Institutions - Gaskins-Scott, Taya (Journal of Interdisciplinary Studies in Education, 2020)
Successful Global Collaborations in Higher Education Institutions is an insightful read. This guide is geared towards university administrators, faculty, and staff who want to join forces with other institutions and make their universities preeminent institutions of the 21st century and beyond. The guide is broken into three sections with the first section being my favorite. The first section highlights King Abdulaziz University (KAU) who is the pioneer institution that created the blueprint for global collaborations. Personally, I have never heard of this university before opening the book. However, King Abdulaziz University collaborated with other academic and research institutions which catapulted them into their success in global ranks. The first section also highlights how institutions could create a climate that will assist in creating global partnerships.